The Effect of Green Country Image on Green Trust on Purchase Intention in the Case of Electric and Hybrid Cars in Indonesia - Halim, Elaine Stacey; Talim, Anastasia; Tarigan, Ruth Srininta; Maer, Maria Natalia Damayanti (Jurnal Riset Ekonomi, Manajemen, dan Bisnis, 2025)
This study investigates the influence of South Korea's green image on Indonesian consumers' trust and purchase intentions regarding electric and hybrid vehicles among Indonesian consumers. As global environmental concerns intensify, understanding how perceptions of a country's environmental commitment influence consumer behavior in the automotive sector is essential for promoting sustainable transportation solutions. This study fills a substantial void in current literature regarding the influence of South Korea's green image on Indonesian consumers, particularly considering Indonesia's escalating environmental challenges. Utilizing an online survey administered to Indonesian participants, the study employs PLS-SEM to investigate the relationships among green country image, green trust, and purchase intentions. The findings reveal that South Korea’s cognitive green image positively correlates purchase intentions, while its affective green image significantly impacts both trust and purchasing decisions. However, the study also finds that affective dimensions do not directly translate into purchase intentions, suggesting that emotional connections may be insufficient without corresponding cognitive evaluations. The results underscore the importance of a robust green country image in enhancing consumer trust and encouraging purchases of environmentally friendly vehicles. Consequently, marketers should strategically leverage both rational and emotional aspects of national image in their campaigns to effectively influence consumer attitudes and behaviors within Indonesia's automotive market. This research emphasizes the necessity for companies and policymakers to prioritize strong environmental commitments in their marketing strategies to foster sustainable transportation solutions.